A case study investigation of the neuropsychological profile of a rugby player with a history of multiple concussions - Case, Stephanie (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
sustained multiple concussions may be at risk of cumulative impairment. The role of neuropsychological testing in the management of sports-related concussion is a contentious and challenging issue which has gained credibility given the lack of clear and well-established guidelines pertaining to the diagnosis, assessment and return-to-play decisions following concussion. Despite various traditional paper and pencil tests being shown to be effective indicators of postconcussive neuropsychological dysfunction, testing has not been widely implemented, due to time- and labour-demands. ImPACT, a computer-based neuropsychological assessment instrument, has been recognised as a valid and reliable tool in the monitoring of athletes' symptoms and neurocognitive functioning preseason and postconcussion. As a part of larger-scale concussion research conducted on top-team university rugby players, this is an in-depth case study conducted on a 20-year old participant with a history of multiple concussions, who was referred following a concussion sustained during the season. The objectives of the study were: (i) to determine the sensitivity of ImPACT versus WAIS-III Digit Span and Trail Making Test during the acute postconcussive phase; and (ii) to examine the sensitivity of ImPACT versus a comprehensive battery of neuropsychological tests to possible residual deficits as a result of the multiple concussions. ImPACT was determined to be more sensitive to acute postconcussive impairment following concussion than Digit Span and Trail Making Test. Furthermore, the ImPACT preseason baseline scores appear to be sensitive to neurocognitive dysfunction, possibly due to cumulative concussive injuries.
Keywords: Rugby football injuries; Brain -- Concussion -- Complications; Neuropsychological tests; Head -- Wounds and injuries -- Complications; Sports injuries -- Psychological aspects